Monitoring the structural integrity of large concrete dams: the case of Cabril dam, Portugal - Oliveira, S. (2011)
The safety control of large dams under static and dynamic loads, involving observation data and numerical modeling, is now one of the challenges of structural engineering. The complexity of the dam-reservoir-foundation geometry, the presence of different types of discontinuities, the water-structure interaction, the influence of thermal and water level variations, the development of deterioration processes over time and the occurrence of exceptional events such as major floods or earthquakes, makes the structural safety control of large dams an activity that requires a continuous updating, both in terms of the equipment for measuring, transmission, and storage of the observation data, and in terms of computer applications to support the automation process of collecting, processing, analysis and management of all information required to the safety control. The recent LNEC and EDP experience on the revision of the monitoring system of Cabril dam, the highest portuguese arch dam, is presented as a case study in this paper. After a brief presentation of the main dam characteristics – a 57 year old dam with some cracking problems since the first filling and a swelling process that has been recently detected - it is described: i) a new system that was recently installed for the continuous measurement of dam vibrations; and ii) an experience on the use of laser scan technology and digital imagery for measuring dam displacements and to support assisted visual inspections on Cabril dam.